2002
DOI: 10.1159/000069364
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal 6-Hydroxydopamine Administration to Mice Is Fatal

Abstract: Depletion of dopamine in adult rats by treatment with the neurotoxin 6-hydroxydopamine (6-OHDA) causes severe deficits in feeding, drinking, and movement that often lead to death. However, when neonatal rats are treated similarly, they survive normally, suggesting that compensatory adaptation to dopamine depletion occurs. In contrast, dopamine-deficient mice that have a selective genetic deficiency in dopamine production die 2–4 weeks after birth. Thus, we tested the hypothesis that killing dopaminergic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, subsequent experiments suggest that the lesions were incomplete in those studies, because surviving rats died if residual dopamine synthesis was inhibited 21,22 . We demonstrated that neonatal ablation of dopamine neurons in dopamine‐deficient (DD) mice does not rescue them, contrary to what would be predicted if killing the neurons allowed dopamine‐independent compensatory adaptations 23 . Furthermore, killing dopamine neurons of DD mice does not hasten starvation, indicating that these neurons do not make other signaling molecules that are essential for survival.…”
Section: History Of Dopamine's Role In Mediating Motivationmentioning
confidence: 86%
See 1 more Smart Citation
“…However, subsequent experiments suggest that the lesions were incomplete in those studies, because surviving rats died if residual dopamine synthesis was inhibited 21,22 . We demonstrated that neonatal ablation of dopamine neurons in dopamine‐deficient (DD) mice does not rescue them, contrary to what would be predicted if killing the neurons allowed dopamine‐independent compensatory adaptations 23 . Furthermore, killing dopamine neurons of DD mice does not hasten starvation, indicating that these neurons do not make other signaling molecules that are essential for survival.…”
Section: History Of Dopamine's Role In Mediating Motivationmentioning
confidence: 86%
“…21,22 We demonstrated that neonatal ablation of dopamine neurons in dopamine-deficient (DD) mice does not rescue them, contrary to what would be predicted if killing the neurons allowed dopamine-independent compensatory adaptations. 23 Furthermore, killing dopamine neurons of DD mice does not hasten starvation, indicating that these neurons do not make other signaling molecules that are essential for survival. Because complete bilateral 6-OHDA lesions produce severe aphagia that requires hand-feeding to keep animals alive, those animals are difficult to maintain and to study.…”
Section: History Of Dopamine's Role In Mediating Motivationmentioning
confidence: 99%
“…However, these models make no distinction between loss of DA signaling versus loss of DA neurons and do not separate performance from cognitive deficits. They have also been difficult to interpret because rodents with complete lesions are very hypoactive and can only be kept alive by forced feeding (38,47); the animals that eat on their own have incomplete lesions (48). Because restoring DA to 5% of normal levels is sufficient for mice to eat adequately (29), we argue that most experiments performed with DA lesions in the dorsal striatum were done on animals with incomplete lesions.…”
Section: Object Memory and Visuospatial Learning Are Partially Restormentioning
confidence: 99%